Thinking and Learning the Glide Technique in Shot Put among Students of the College of Physical Education and Sports Sciences - Sinan Abdulhussein Ali (Pubmedia Jurnal Pendidikan Olahraga, 2026)
Zaharic’s model was employed in this study in order to develop reflective thinking in the students of Physical Education and Sports Sciences as well as to master the glide technique in shot put. The importance of the scientific value of the study is that it keeps pace with the modern tendency to add self-regulated learning in the learning process in order to develop higher mental skills. To reach the goal, the experiment was run with two groups design (experimental and control). The study sample comprised (20) second-year students. The subjects were distributed randomly and equally on two groups. The study was done for 2 months duration which was of 4 units in a week, as the experimental group implemented Zahorik model control group implemented the regular method. After processing the data, the results of the reflective thinking scale and technical performance test show that the experimental group in the post-test for both variables has significant superiority. According to that, it was confirmed that Zahorik model gives a positive contribution to the variables. The overall conclusion of this study indicates that Zahorik's model is an effective educational model for developing reflective thinking and learning shot put glide technique. Moreover, it provides a functional learning situation. This functional learning situation combines cognitive construction and motor application in an integrated manner.